Studi Penyusunan Tabel Volume Lokal Jenis-Jenis Komersial Ekspor di Hutan Mangrove HPH PT. Bina Lestari, Propinsi Dati I Riau - Rieny Marlia; Suwarno Sutarahardja; Budi Prihanto (Jurnal Manajemen Hutan Tropika, 1999)
Rhizophora apiculata (bakau) and Bruguiera gymnorrhiza (tumu) in are commercial export species of mangrove forest. Both species are the dominant species in mangrove forest at HPH PT. Bina Lestari I (Gaung and Mandah River Forest Complexs), Riau Province.  To ensure a continuous production of wood, detailed knowledge about standing stock obtained through inventories is needed. To facilitate and improve the reliability of inventories, volume table is indispensable.  The results represent mensurational study on 100 purposive selected sample trees, 50 samples for each species. Two models are developed, in which, bakau used a volume/diameter function (tariffs),while the other (tumu) used volume/diameter/height function to estimate the volume of individual trees. The dveloped tariffs of bakau is : V = 0.000107152 D 2.4; while the tariffs of tumu is : V = 0.000134896 D1.61 T, where V is volume from the base of tree up to diameter limit 7 cm outside bark and without root/shrunk; D is Diameter outside bark at 20 cm over the root/shrunk; and H is Total tree height.